Chapter Professionalization of Teachers and Problematization Processes - Maccario, Daniela (Studies on Adult Learning and Education, 2018)
This article presents the path and the results of research aimed at developing innovative teaching approaches in the context of academic courses for in-service teachers as regards their professional training